![4 {x}^{2} - \sqrt{2} - 3 4 {x}^{2} - \sqrt{2} - 3](https://tex.z-dn.net/?f=4+%7Bx%7D%5E%7B2%7D++-++%5Csqrt%7B2%7D++-+3)
Answers
Answered by
0
Answer:
use of Sridhara or Sridhara Acharya’s
Method for Solution of Quadratic
Step-by-step explanation:
ax² + bx = c ,
we have 4a²x² + 4abx = 4ac,
and then 4a²x² + 4abx + b² = 4ac + b² .
Or, (2ax + b)² = 4ac + b² . A square root extraction gives
2ax + b = √(4ac + b²)
⇒ x = [√(4ac + b²) - b]/2a
Answered by
0
Answer:
PLEASE COMPLETE YOUR QUESTION
Step-by-step explanation:
Similar questions
Computer Science,
1 month ago
Math,
1 month ago
English,
1 month ago
English,
3 months ago
Math,
11 months ago